2016
DOI: 10.7771/2159-6670.1137
|View full text |Cite
|
Sign up to set email alerts
|

Safety Professional’s Perception of the Relationship Between Safety Management Systems and Safety Culture

Abstract: The purpose of this qualitative study was to investigate the relationship between the elements/processes of safety management systems (SMSs) and their impact on safety culture at collegiate flight training institutions. Research questions addressed the following: different approaches to developing and implementing an SMS, different approaches to the assessment of safety culture, and the relationship between elements/processes of an SMS and a strong safety culture. A semistructured interview protocol was used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Also, enhanced certificate training improve pilot's competency to mitigate the risk of VMC and IMC 2 mishaps. Robertson (2016) study based on interviews of five safety professionals from five flight training institutions and found that a confidential hazard-reporting system was fundamental in building a strong safety culture, which includes the SMS implementation, the changes that being made from the hazard reporting and safety culture assessment. Also, the relationship between safety culture and SMS is circular.…”
Section: Ato and Safety Risksmentioning
confidence: 99%
“…Also, enhanced certificate training improve pilot's competency to mitigate the risk of VMC and IMC 2 mishaps. Robertson (2016) study based on interviews of five safety professionals from five flight training institutions and found that a confidential hazard-reporting system was fundamental in building a strong safety culture, which includes the SMS implementation, the changes that being made from the hazard reporting and safety culture assessment. Also, the relationship between safety culture and SMS is circular.…”
Section: Ato and Safety Risksmentioning
confidence: 99%
“…This part of a SMS deals with internal and external auditing, data collection, and performance measuring. A critical element of safety assurance is the constant inflow of objective error reporting data submitted through voluntary reporting systems (VRSs) (Robertson, 2016). Safety assurance is an important SMS function as it verifies that risks are being identified, mitigated and controlled.…”
Section: Purpose Of the Aviation Smsmentioning
confidence: 99%
“…However, few studies exist addressing the relationship between SMS implementation and its impact on developing a strong safety culture (McNeely, 2012). Few studies have been conducted that have attempted to identify if there is a relationship between SMS implementation and safety culture in collegiate flight schools (Robertson, 2016). The purpose of this study is to examine the relationship between SMS implementation and safety culture at collegiate flight schools.…”
Section: Introductionmentioning
confidence: 99%
“…Other elements of SMS that contributed were a strong training program and the SRM five-step processes. Robertson (2016) recommended that both quantitative and qualitative studies continue to examine the relationship between SMS and safety culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation